Odpowiedzi

Najlepsza Odpowiedź!
2009-10-28T15:55:08+01:00
A)
(x+1)(x+1)=(x-1)(x-1)
x²+2x+1=x²-2x+1
x²+2x-x²+2x=1-1
4x=0/÷4
x=0

b)
x²*4=(2x+1)(2x+1)
4x²=4x²+4x+1
4x²-4x²-4x=1
-4x=1/÷(-4)
x=-¼

c)
(x+2)*4x=(2x+1)(2x-1)
4x²+8x=4x²-2x+2x-1
4x²+8x-4x²-2x+2x=1
8x=1/÷8
x=⅛


Te skroty w pierwszym i drugim przykladzie sa przez to ze zastosowalem tam wzory skroconego mnozenia.
2009-10-28T15:58:05+01:00
C) 4x(x + 2) = (2x -1)(2x + 1)
4x² + 8x = 4x² + 2x - 2x - 1
4x² + 8x = 4x² - 1
8x = -1
x = - ⅛


b) 4x² = ( 2x + 4 )( 2x + 4 )
4x² = 4x² + 8x + 8x + 16
4x² = 4x² + 16x + 16
-16x = 16
x = -1

a) (x + 1)(x + 1) = (x - 1)(x - 1)
x² + x + x + 1 = x² - x - x + 1
x² + 2x + 1 = x² - 2x + 1
2x + 2x = 1 - 1
4x = 0
x = 0